2021
DOI: 10.1038/s41598-021-95792-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigation and nitrogen on chlorophyll content, dry matter and nitrogen accumulation in sugar beet (Beta vulgaris L.)

Abstract: A 2-year field experiment was conducted to analyze the growth conditions, physical features, yield, and nitrogen use efficiency (NUE) of sugar-beet under limited irrigation conditions in northeast of China. A cultivar H003 was used as plant materials; six treatments (C1–C6) were included: C1, no nitrogen applied, rain-fed; C2, nitrogen (120.00 kg ha−1), rain-fed; C3, no nitrogen applied, hole irrigation for seeding; C4, nitrogen (120.00 kg ha−1), hole irrigation for seeding; C5, no nitrogen applied, hole irrig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 31 publications
7
28
2
Order By: Relevance
“…Previously, it has been reported that the application of only the NO 3 − form of N reduced the chlorophyll contents. Our results are in accordance with previous studies that reported that the relative chlorophyll contents were significantly improved by the 25% NH 4 +/ 75% NO 3 − ratio [ 40 , 41 , 42 ]. The application of NH 4 + /NO 3 − ratios influenced chlorophyll synthesis and ultimately increased the chlorophyll contents of the plant [ 42 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Previously, it has been reported that the application of only the NO 3 − form of N reduced the chlorophyll contents. Our results are in accordance with previous studies that reported that the relative chlorophyll contents were significantly improved by the 25% NH 4 +/ 75% NO 3 − ratio [ 40 , 41 , 42 ]. The application of NH 4 + /NO 3 − ratios influenced chlorophyll synthesis and ultimately increased the chlorophyll contents of the plant [ 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…The chlorophyll synthesis is associated with different N sources, which are ultimately correlated with the photosynthesis rate and determine the final crop yield [ 41 ]. The application of NH 4 + /NO 3 − ratios increases the surface area of the plant by increasing the photosynthesis rate and ultimately increases the plant biomass.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the composition of photosynthetic pigments is very variable for different species [150,161]; this composition changes regarding the individual development of the plant [162][163][164], and it can be strongly dependent on local environmental conditions [161]. Particularly, the mineral nutrition is an important factor influencing concentrations of pigments in plants; e.g., changes in the nitrogen nutrition can influence concentrations of photosynthetic pigments and the content of RUBISCO, which is the key photosynthetic enzyme [7,[165][166][167][168]. Thus, heterogeneity of the pigment composition can be the long-term factor modifying the efficiency of the plant remote sensing.…”
Section: Variability Of Plantsmentioning
confidence: 99%
“…The most important environmental factors affecting plant growth are moisture and nutrient availability and their interactions in soil. Drought alters the photosynthetic machinery of plants, chlorophyll synthesis, biomass allocation, and other major physiological activities of plants [12][13][14]. The interacting effects of water shortage and nutrient deficiency limit plant growth and forest plantation productivity, particularly in desertified areas [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The interacting effects of water shortage and nutrient deficiency limit plant growth and forest plantation productivity, particularly in desertified areas [15,16]. An experiment has shown that both fertilizer and irrigation amount explained the increase in chlorophyll content of plants under limited irrigation conditions in China, such that the no fertilizer and irrigation treatments resulted in the lowest chlorophyll content [12]. A study has also found that the medium amount of both fertilizer and water resulted in higher growth performance, number of new shoots, chlorophyll content, and leaf soluble sugar concentration compared with high and low amounts of fertilizer and irrigation treatments [17].…”
Section: Introductionmentioning
confidence: 99%